'Emotional turbulence': the development of symbolic thinking in the psychotherapeutic treatment of an adolescent girl. Issue 1 (2nd January 2018) - Wright, Hilary
Abstract: This paper is drawn from doctoral research which analysed clinical data from the once weekly psychotherapy of a young person who experienced both gender identity dysphoria and an eating disorder and whose depression had proved resistant to other interventions. Based on the psychoanalytic thinking of Klein, Segal, Bion and others regarding the role of symbolisation in development, the links between symbol formation, the depressive position and the negotiation of the Oedipus complex are outlined. Special attention is given to current thinking about the nature and genesis of gender identity dysphoria in the light of these concepts. The association with autistic features for a number of cases is briefly explored. In the light of these theoretical links, findings from the study are used to investigate and illustrate the movement this patient made within her therapy from an emotionally turbulent position where concrete thinking was manifest, to a more symbolic way of thinking that allowed emotional change, and less concrete acting out. Clinical narrative excerpts as well as findings from the study are used to discuss the progress made by the patient and to evaluate how her journey may inform future practice.